Asian monetary integration : coping with a new monetary order after the global crisis - Moon, Woosik; Rhee., Yeongseop (Cheltenham Edward Elgar Publishing Ltd.)
Summary: Numerous ideas for monetary and financial cooperation in East Asia have been proposed both within and outside the region since the financial crisis in Asia. Despite this strong level of interest, however, there are few studies that aim to comprehensively address the issue from multiple perspectives. This insightful book redresses the balance and illustrates how East Asian countries plan to take advantage of their rising economic power in rearranging the new international monetary and financial order in the post-crisis era. The expert contributors examine the history, conditions and current efforts towards monetary integration in Asia and explore possible future paths, highlighting the roles and perspectives of East Asian countries in the integration process. They consider how East Asian economies could establish their own zone of monetary stability, and show that monetary stability cannot be separately addressed from the issues of economic growth and solidarity. Without economic growth and solidarity, there would be no purpose in pursuing monetary integration, therefore all three challenges must be simultaneously addressed. Against this backdrop, the book tackles the issues of East Asian monetary integration underpinned by the broad framework of economic growth and solidarity. Scholars of economics, monetary integration, Asian studies and regionalism will find this book to be an illuminating and thought-provoking read.
1. Introduction -- 2. Silver and the Origin of Asian Currencies -- 3. Destined to Fail? The History of the Yen before the Second World War -- 4. Globalization and Regionalization of East Asian Economies -- 5. Conditions for Monetary Integration in East Asia -- 6. Need for Regional Monetary and Financial Arrangements in East Asia -- 7. The Beginning of Monetary Cooperation in East Asia and the Chiang Mai Initiative -- 8. Financial Market Integration and Asian Bond Market Initiatives -- 9. Exchange Rate Coordination and Regional Currency Unit -- 10. The Road towards a Monetary Union -- 11. Hurdles and Challenges
Summary from British Library catogues
Includes bibliographical references (p. 210-227) and index
Keywords: International economics; EXCHANGE RATE; MONETARY POLICY; FREE TRADE; POVERTY; ECONOMIC INTEGRATION; ECONOMIC CONDITIONS; EAST ASIA